HYPERURICEMIA AS A RISK FACTOR OF ARTERIAL HYPERTENSION - Ye. L. Kovalenko; O. K. Melekhovets; V. F. Orlovskiy; Yu. V. Melekhovets (Східноукраїнський медичний журнал, 2019)
Introduction. Among the population of Central and Eastern Europe, hyperuricemia (HU) prevalence is 28 % in female and 23 % in male. In 2018, European Society of Hypertension has officially included HU to the independent risk factors for AH.